Citizenship Education and Exclusion: An Analysis of Authorized History Textbooks and Children’s Books in Ontario, 1866-1950 - Roy, Philip (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2025)
Since 1866, the Ontario Department of Education has facilitated the teaching of citizenship education through its authorization of history textbooks. Using a critical discourse analysis framework constructed from the theories and analyses of five prominent scholars: Reinhart Koselleck, Edward Said, Quentin Skinner, Ken Osborne and Ian McKay, this paper explores how a principle of exclusion was pivotal in supporting an Anglocentric nationalist agenda in the historical narratives of the texts. History textbooks are examined for evidence of the exclusion of women, Indigenous peoples, immigrants, people of colour, and the working class. This exploration is compared with an examination of children’s books written during the same period. The aim of the comparison is to identify possible alternative citizenship ideals that emerge in fictional narratives as compared with authorized historical narratives, a comparison that, as yet, has not been done before.